Distinguishing Islam from Islamism: Bassam Tibi's Insights on Fundamentalism and Religious Politics - Rojaya, Rojaya; Rahman, Mohammad Taufiq (UIN Sunan Gunung Djati Bandung, 2025)
This study examines Bassam Tibi’s perspective on fundamentalism and critiques its limitations. Using textual and documentary study methods, this study examines fundamentalism as an important phenomenon in the modern era. Bassam Tibi, a prominent Muslim thinker and professor, distinguishes Islam as a religion and civilization from Islamism as a politicized ideology aimed at socio-political and economic goals. He critiques Islamism as a fundamentalism that abuses religious principles for political purposes. Tibi advocates the modernization of Islamic education to promote cultural progress and counter fundamentalist ideology. However, Tibi’s perspective has weaknesses. He oversimplifies the diversity of fundamentalist movements, conflates fundamentalism with radicalism and terrorism, and emphasizes political solutions while ignoring cultural approaches. This study highlights the need for a more nuanced understanding of fundamentalism, taking into account its socio-political roots and diverse manifestations while exploring alternative strategies to address its challenges in Muslim societies. Tibi’s thinking remains valuable but needs refinement to better address the complexities of fundamentalism in the contemporary context.